Paradigm Shift in Clinical Practice of Induction of Labor: A Single Centre Experience and Literature Review - Tshering, Sangay; Dorji, Namkha (Bangladesh Journal of Obstetrics & Gynaecology, 2020)
The burden of induction of labor is rising globally. The clinical practice guidelines on induction of labor is time bound and must be built on evidence based practice. The scope of update must be contextual to the local setting with expected positive implications. Any recommendations or change in practice must ensure feasibility, accessibility and practicality. We present a review on IOL adapted to our setting. Bangladesh J Obstet Gynaecol, 2020; Vol. 35(1): 37-40